AN ANALYSIS OF GRAMMATICAL DEVIATION IN OLIVIA RODRIGO’S GUTS USING LEECH’S THEORY - Mamengko, Villareal; Lumban Raja, Putri Jesika; Lase, Helena Wenefrida; Mogea, Tini; Pabur, Herminus Efrando (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Grammatical deviation serves as a crucial stylistic tool in contemporary music lyrics, yet its strategic use by female pop artists to convey authenticity and emotion remains underexplored. This study addresses that gap by analyzing grammatical deviations in Olivia Rodrigo’s GUTS (2023) album through Leech’s (1969) framework. Using a qualitative content analysis approach, the researcher examined all twelve songs, identifying, classifying, and interpreting deviations in structure and form. The findings reveal 50 instances of grammatical deviation categorized into omission, morphological deviation, informal contractions, verb tense/aspect deviation, lexical deviation, and repetition. Omission emerged as the most frequent type, reflecting the artist’s conversational tone and rhythmic compression, while morphological deviations and contractions highlight spoken authenticity. Less frequent yet impactful deviations, such as taboo words and repetition, intensify emotional expression and rhythm. Overall, the study concludes that grammatical deviations in GUTS are deliberate stylistic choices rather than linguistic errors, enhancing Rodrigo’s identity, relatability, and emotional realism. These findings contribute to linguistic stylistics by demonstrating how contemporary female pop artists creatively manipulate grammar to express individuality and connect with modern audiences.